Lessons from COVID-19 plain chest radiographs on pathophysiology, early diagnosis and therapeutics - Ndaba Sibusiso; Sabela Tholakele; Mnqwazi Chizama; Sithole Sthembiso; Sithole Nokwanda; Mashigo Boitumelo; Mhlana Nontembiso; Ntshalintshali Sipho (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2020)
Introduction: There are multiple radiographic manifestations of COVID-19 described in recent literature on plain chest radiographs and lung CT scans. We discuss observations on apparent similarities and differences seen on plain chest radiographs of confirmed COVID-19 cases with clinically mild, moderate and severe form of disease.  Material and method: We randomly selected 3 cases of COVID-19 with mild, moderate and severe disease, and compared the radiological findings on plain chest radiographs. Results: The radiographic observations suggest that poorly aerated regions of the lung are affected early during the disease course. The inference is that improving the degree of lung aeration may limit the spread of the disease on the remainder of the lung parenchyma. Therefore, early oxygen supplementation therapy may prevent progression of a clinically mild COVID-19 case to moderate or severe form of disease. Conclusion: Early plain chest radiographs may assist to increase the index of suspicion in a COVID-19 Patient Under Investigation (PUI) with pending RT-PCR results. The degree of lung aeration in COVID-19 correlates with the disease severity. Early oxygen therapy in mild cases may prevent progression of COVID-19. Larger studies are recommended to ascertain the statistical significance of these findings.